Comparison of the relationship between key demographic features and physical activity levels across 22 countries - Chung Gun Lee; Elizabeth Kwon; Jason Paltzer; Chukwuemeka N. Okafor; Tyler J. VanderWeele; Byron R. Johnson; Joo Hee Choi (BMC Public Health)
Abstract Background The present study aims to examine global trends in physical activity levels and explore the potential influence of demographic factors on physical activity participation. Methods Using data from the Global Flourishing Study (GFS), which includes 202,898 participants from 22 geographically and culturally diverse countries, we assessed the average number of days of physical activity across various demographic groups (age, gender, marital status, employment, religious service attendance, education, immigration status) and across different countries. Results While patterns varied across the 22 countries, certain consistent trends overall emerged. Physical activity levels were higher among individuals aged 60–69 compared to younger and older age groups, men compared to women, and those in domestic partnerships compared to single individuals. Higher activity levels were also observed among the self-employed, those with higher educational attainment, frequent religious service attendees, and individuals born in the country of residence compared to immigrants. Notably, Egypt reported the lowest average number of physical activity days, whereas the Philippines reported the highest. Conclusions These results contribute to a deeper understanding of the sociodemographic disparities in physical activity participation. By documenting physical activity patterns across key demographic groups and countries worldwide, this study provides valuable insights into the social determinants of physical activity behavior.